Estudo da via PI3K/AKT/PTEN no câncer: revisão sistemática com metanálise da metilação de PTEN em carcinomas e análise da imunoexpressão de PTEN, PI3K, S6K1 e GSK-3β em carcinomas de células escamosas orais - Luna, Ealber Carvalho Macedo (2019)
Oral squamous cell carcinoma (OSCC) represents more than 90% of oral cavity malignancies, the most common cancer being in this location in Brazil. Studies in the area focus on investigating the molecular basis of tumor development and progression. However, recent research investigates epigenetic changes as critical changes in carcinogenesis and, among these modifications, DNA methylation is included. PTEN gene is a tumor suppressor gene that participates in the PI3K / Akt / PTEN one of deregulated pathways studied, and more recently in carcinogenesis. Thus, this thesis consists of two sections, which aims respectively: 1) performing a systematic review and meta-analysis of the methylation of PTEN gene in carcinoma; 2) to analyze the immunoexpression of PTEN, PI3K, S6K1 and GSK-3β in OSCC samples. Chapter 1, a systematic review was performed with a meta-analysis registered in the PROSPERO database. The search strategies were performed in seven databases, including the gray literature. 38 studies were included for systematic review and meta-analysis to 12. The primary outcome was assessed the relationship between PTEN methylation profile of human carcinomas, suggesting that epigenetic changes may be associated with tumorigenesis process. Chapter 2, the immunohistochemical expression of PTEN, PI3K, S6K1 and GSK-3β in oral squamous cell carcinoma samples was analyzed. Were selected 76 cases of OSCC from the Cancer Institute of Ceará (ICC). A TMA (Tissue microarrayer) technique was performed, analyzing the cases of OSCC, perilesional area and lymph node. Specimens were subjected to the Streptavidin-biotin-peroxidase immunohistochemical technique using the antibodies of the brand Abcam PTEN (1: 400), GSK-3β (1: 100), S6K1 (1: 200) and PI3K (1: 400). Immunopositive cells for these markers were counted, as well as the location and intensity of labeling, and the mean ± SEM of the cell counts and calculated histoscores were expressed, which were analyzed by the Pearson chi-square test. The categorical data were expressed in absolute frequency and compared by Fisher's exact test or Pearson's chi-square, adopting the level of significance of p <0.05. Statistically significant differences were observed between cytoplasmic PTEN (p <0.001), PI3K (p <0.001) and GSK-3β (p <0.001) cytoplasmic markers, when comparing tumor samples, perilesion and lymph node metastasis. Regarding PTEN marking in the nucleus (p = 0.351) and S6K1 (p = 0.999), no statistical differences were observed. It is suggested that the expression of these proteins may be involved in the oral carcinogenesis process.